Cost optimization of three-dimensional beamless reinforced concrete shear-wall systems via genetic algorithm - Atabay, Senay (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this present work, a cost optimization has been done for r/c structural system by genetic algorithm method. In the optimization problem the shear-wall dimensions has been considered as design variables and it has been aimed at searching the optimum shear-wall dimensions that minimize total material cost of shear-wall. The constraints of structural optimization problem are constructed according to the requirements of the r/c specification so-called as TS 500. and the seismic code of Turkey which is put into effect on 1998. The standard structural design procedure requires the predetermination of the dimensions of load carrying members that is generally based oil designer's engineering skill, experience and intuition. In practical design applications, final dimensions are generally selected as one of the most suitable ones among numerous design selections that satisfy the regulations. However, the most of these design alternatives may not be economical, and the most economical design Could only be provided by a more elaborated optimization procedure. A computer program is also developed for determining the optimum shear-wall dimensions for the minimum cost design of structural systems. The proposed algorithm minimizes structural cost including the cost of concrete and the reinforcement, wherein the costs related to transportation, workmanship and formwork prices are not included. An 13 story and beamless shear-wall system is presented as a numerical example. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Genetic algorithm; Shear-wall systems; Cost optimization; Structural optimization; ARTIFICIAL NEURAL-NETWORK; DESIGN; Computer Science; Engineering; Operations Research & Management Science